2020
DOI: 10.3390/antiox9111127
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Relaxes Human Uterine Artery via Activating Smooth Muscle BKCa Channels

Abstract: Opening of large conductance calcium-activated and voltage-dependent potassium (BKCa) channels hyperpolarizes plasma membranes of smooth muscle (SM) to cause vasodilation, underling a key mechanism for mediating uterine artery (UA) dilation in pregnancy. Hydrogen sulfide (H2S) has been recently identified as a new UA vasodilator, yet the mechanism underlying H2S-induced UA dilation is unknown. Here, we tested whether H2S activated BKCa channels in human UA smooth muscle cells (hUASMC) to mediate UA relaxation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 76 publications
(77 reference statements)
2
36
0
Order By: Relevance
“…Published studies showed that ion channels undergo direct regulation by H 2 S. Differing effects of H 2 S were shown for BK Ca channels. H 2 S potentiated BK Ca currents in human uterine artery smooth muscle cells (Li et al, 2020). H 2 S also increased the activity of BK Ca channels in rat pituitary tumor cells, and this effect was linked to its action on sulfhydryl groups of the channel protein (Sitdikova et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Published studies showed that ion channels undergo direct regulation by H 2 S. Differing effects of H 2 S were shown for BK Ca channels. H 2 S potentiated BK Ca currents in human uterine artery smooth muscle cells (Li et al, 2020). H 2 S also increased the activity of BK Ca channels in rat pituitary tumor cells, and this effect was linked to its action on sulfhydryl groups of the channel protein (Sitdikova et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, whether and how mitoBK Ca activity is modulated by H 2 S remains an intriguing issue. Previous research on the impact of H 2 S on the activity of BK Ca channels is ambiguous, thus showing either channel activation (Jackson-Weaver et al, 2013, Li et al, 2020 or inhibition (Fernandes et al, 2015, Li et al, 2010, Telezhkin et al, 2010. Therefore, further studies are needed in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, stimulation of H 2 S production with PLP enzyme significantly elevates H 2 S levels and improves vascular relaxation together with oxidative and nitrosative statuses in adult rats [ 95 ]. Similarly, treatment with NaHS has also been shown to induce the relaxation of human uterine artery, partly by triggering the large conductance calcium-activated and voltage-dependent K + (BK) channels [ 96 ]. An isothiocyanate vasodilating compound, sulforaphane, has also been reported to induce its effect by activating K ATP and BK channels in a CBS/CSE/H 2 S-dependent manner [ 97 ].…”
Section: Role Of H 2 S In Vascular Functionmentioning
confidence: 99%
“…The γ1 subunit also increases BK Ca channel activation and promotes vasodilation of uterine arteries. Notably, the BK Ca channel mediates uterine vasodilation induced by NO, H 2 S, calcitonin gene-related peptide and adrenomedullin [55,56,210,214,215]. However, the vasodilation of human placenta vessels induced by H 2 S is mediated by NO and ATP-sensitive K + (K ATP ) channels [133].…”
Section: Ca 2+ Spark/stoc Couplingmentioning
confidence: 99%